The effects of absenteeism on nurses remaining on duty at a tertiary hospital of Limpopo province - Masenyani O. Mbombi; Tebogo M. Mothiba; Rabelani N. Malema; Mokgadi Malatji (AOSIS, 2018)
Background: Absenteeism is a global problem in the working force and this is no exception in the nursing profession. Much attention has been drawn to factors that contribute to absenteeism; however, little attention has been placed on the effects of absenteeism on nurses remaining on duty by their colleagues. Nurses absent themselves leaving behind their colleagues to execute their part of work. Objectives: To investigate the effects of absenteeism on nurses who remained on duty at a tertiary hospital in Limpopo province. Method: A quantitative descriptive research approach was chosen to enable the researchers to achieve the research aim. Data collected using structured questionnaires were analysed by descriptive statistics. Results: The findings indicated that absenteeism has an effect on both the nurses' psychological and professional well-being, as well as the quality of patient care provided as a result of psychological stress, low morale of nurses and increased workload. The study further revealed the provision of substandard care to patients by those nurses who are remaining on duty, resulting in risk of medical errors that could jeopardise their professional credibility. Therefore, absenteeism creates an unhealthy working environment for nurses remaining on duty. Conclusion: Nurse managers should provide platforms to address psychological and professional problems experienced by nurses remaining on duty. The study further recommends the introduction of policies that would address absenteeism in the workplace and how nurses who remain on duty could be assisted with the workload of colleagues who continuously absent themselves.